Biomassa e diversidade microbiana em solo adubado com biocarvão e cultivado com cana-de-açúcar - Érika Manuela Gonçalves Lopes (2023)
Biochar is a product generated from the pyrolysis of biomass and it has been used as a corrective for agricultural soils. The interest in biochar is due to its ability to sequester C from the soil, in addition to promoting benefits in agricultural areas through changes in the physical and chemical properties of the soil. However, information of the interaction of biochar with biological properties are still incipient. In this sense, the present work aimed to investigate the effects of biochar on the microbial community and enzymatic activity of the soil over time. During two consecutive years, they were collected soil samples from the sugarcane planting line fertilized with biochar. The planting of sugarcane was carried out, in 2017, in a randomized block design, factorial 5 x 2, with four replications, with five doses of biochar (0, 10, 20, 30 and 40 Mg ha-1), with and without soil fertility correction. They were evaluated the activities of the enzymes β-glucosidase, acid phosphatase, arylsulfatase, urease and fluorescein diacetate (FDA), in addition to the carbon content of microbial biomass (MBC), soil basal respiration (SBR), total organic carbon (SOC), metabolic quotient (qCO2), microbial quotient (qMIC) and Shannon index. The interaction effects between biochar doses and NPK fertilization were significant (p ≤ 0.05) for contents of MBC, SBR, qCO2, qMIC and Shannon index and for the enzymes β-glucosidase, arylsulfatase, acid phosphatase and urease. It was not observed interaction between the factors for SOC and the ADF enzyme. As for the enzymatic activity of the soil, the doses of biochar promoted an increase in all the enzymes analyzed, with the exception of only arylsulfatase in soil with the addition of NPK. In general, treatments with chemical fertilizer showed higher enzymatic activity, with the exception of acid phosphatase, regardless of the dose of biochar and urease in treatments with doses of biochar lower than 20 Mg ha-1. As for the biological activity of the soil, the increase in biochar doses increased the MBC, SBR, qCO2, qMIC and the Shannon index, being observed the highest values in soils that received intermediate doses of biochar (10-30 Mg ha-1). The biochar doses linearly increased the SOC content. Treatments with chemical fertilizer showed, in general, the highest soil biological activity. They were observed higher values of the Shannon index, SBR and β-glucosidase and urease enzymes in the third year after the implantation of the sugarcane field in the treatments with the NPK addition. It was concluded that the use of biochar can increase enzymatic and biological activity and carbon sequestration in the soil.